Integration of Women in Combat Operations and Warfare: Possibilities of Integration into Pakistan Armed Forces - Shamaila Amir; Saman Zaid (Vojenské rozhledy, 2023)
The participation of women in the armed forces creates many challenges to their integration in a masculine-dominated mechanism. Traditionally, military service embodies the macho culture where a certain type of physical strength is required, attainable only through the male frame. The traditional military personnel model represents a young male force that is supported by spouses who stay at home but modern warfare and the inclusion of technology have opened many chances for women to be included in the armed forces. Therefore, the aim of this paper is to highlight various fields of armed forces where women in Pakistan may or may not be suitable to be integrated. The paper descriptively analyzes the participation of women in armed forces in general and in the Pakistan Armed Forces in particular. Recommendations highlight the combat operations relevant to the Pakistan Armed Forces context which women can or cannot be integrated into.